A Theoretical Study of the Dynamic Behavior of Alkane Hydroxylation by a Compound I Model of Cytochrome P450 - Yoshizawa, Kazunari; Kamachi, Takashi; Shiota, Yoshihito (Journal of the American Chemical Society, 2001)
Dynamic aspects of alkane hydroxylation mediated by Compound I of cytochrome P450 are discussed from classical trajectory calculations at the B3LYP level of density functional theory. The nuclei of the reacting system are propagated from a transition state to a reactant or product direction according to classical dynamics on a Born−Oppenheimer potential energy surface. Geometric and energetic changes in both low-spin doublet and high-spin quartet states are followed along the ethane to ethanol reaction pathway, which is partitioned into two chemical steps:  the first is the H-atom abstraction from ethane by the iron−oxo species of Compound I and the second is the rebound step in which the resultant iron−hydroxo complex and the ethyl radical intermediate react to form the ethanol complex. Molecular vibrations of the C−H bond being dissociated and the O−H bond being formed are significantly activated before and after the transition state, respectively, in the H-atom abstraction. The principal reaction coordinate that can represent the first chemical step is the C−H distance or the O−H distance while other geometric parameters remain almost unchanged. The rebound process begins with the iron−hydroxo complex and the ethyl radical intermediate and ends with the formation of the ethanol complex, the essential process in this reaction being the formation of the C−O bond. The H−O−Fe−C dihedral angle corresponds to the principal reaction coordinate for the rebound step. When sufficient kinetic energy is supplied to this rotational mode, the rebound process should efficiently take place. Trajectory calculations suggest that about 200 fs is required for the rebound process under specific initial conditions, in which a small amount of kinetic energy (0.1 kcal/mol) is supplied to the transition state exactly along the reaction coordinate. An important issue about which normal mode of vibration is activated during the hydroxylation reaction is investigated in detail from trajectory calculations. A large part of the kinetic energy is distributed to the C−H and O−H stretching modes before and after the transition state for the H-atom abstraction, respectively, and a small part of the kinetic energy is distributed to the Fe−O and Fe−S stretching modes and some characteristic modes of the porphyrin ring. The porphyrin marker modes of ν 3 and ν 4 that explicitly involve Fe−N stretching motion are effectively enhanced in the hydroxylation reaction. These vibrational modes of the porphyrin ring can play an important role in the energy transfer during the enzymatic process.